2013
DOI: 10.29173/cais245
|View full text |Cite
|
Sign up to set email alerts
|

Mapping User’s Activities and Space Preferences in the Academic Business Library

Abstract: Examines patrons’ use of spaces in a small academic library using observation and GIS technology. A questionnaire was used to assess patrons’ perceptions of space use. Results of the study can guide the design of library spaces and help researchers and librarians better understand patrons’ needs in these settings.Cette communication examine l’utilisation de l’espace-usager d’une petite bibliothèque universitaire par l’observation et la technologie SIRS. Un questionnaire a été utilisé pour évaluer la perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…The topic of access to books and browsing seems to be a low priority for researchers as more items have moved from print to electronic, and more students have off-campus access to databases and electronic resources, which resulted in both decreasing circulation of print items and reduction of reference enquiries in academic libraries. These trends have led to issues of whether or not the physical space of academic libraries still required (Martell, 2008;Silver, 2007;Thomas, 2000), while others see the changes in the use of academic libraries as an augmentation of these institutions as part of the public infrastructure (Simpson, 2007).…”
Section: Development Of Computermentioning
confidence: 99%
See 4 more Smart Citations
“…The topic of access to books and browsing seems to be a low priority for researchers as more items have moved from print to electronic, and more students have off-campus access to databases and electronic resources, which resulted in both decreasing circulation of print items and reduction of reference enquiries in academic libraries. These trends have led to issues of whether or not the physical space of academic libraries still required (Martell, 2008;Silver, 2007;Thomas, 2000), while others see the changes in the use of academic libraries as an augmentation of these institutions as part of the public infrastructure (Simpson, 2007).…”
Section: Development Of Computermentioning
confidence: 99%
“…Although electronic resources are most likely the replacement for print collections, it may be difficult for print collections to be completely replaced by electronic resources, and there is a continuing need for physical space for collection growth and the technology to use both the physical collection and electronic resources (MacWhinnie, 2003;Simpson, 2005). There are several reasons for this:  Books are published in an increasing number every year (MacWhinnie, 2003;Simpson 2007), and libraries continue to acquire large number of books to add to their collections. Martell (2008) found that from the ARL (Association of Research Libraries) Statistics, there were about 358,950,000 total physical volumes held by ARL Libraries in 1995, and it had increased to 470,283,000 (which gives about 31% increases of physical volumes held).…”
Section: Are Electronic Resources Going To Replace Print Collection?mentioning
confidence: 99%
See 3 more Smart Citations